La influencia positiva o negativa de la motivación, autoestima y ansiedad en el proceso de aprendizaje de los estudiantes de la materia Inglés Intermedio Intensivo I del Departamento de Idiomas Extranjeros de la Facultad de Ciencias y Humanidades de la Universidad de El Salvador - Arias Zepeda, Dina Eunise; Cerón, Eveling Cecilia; Ramírez Gutiérrez, Evelyn Yanette; Rivera López, Karen Abigail; Guzmán, Cesar Augusto; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2013)
Some people learn English as a second or foreign language all over the world so it has become an appealing topic to study. Then it was found out there are some factors are present throughout the process, for example: social factors, learning styles, native language, affective factors, and so on. Giving the importance to affective factors, for instance: personality, motivation, empathy, self-esteem, and anxiety among others, some researchers such as Brown (1994), Gardner (1972), Horwitz (1986), among others stated that they are of great impact on English language learning. As affective factors is a broad topic, this work emerged to study the most relevant factors. Moreover, this search has been addressed to explore the influence of motivation, self-esteem, and language anxiety influence positively or negatively students’ English language learning process of Intermediate Intensive English I courses of the Foreign Languages Department, School of Arts and Sciences, University of El Salvador. In fact, they are present in certain activities in student’s learning process.
Incluye anexos
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2013
Bibliográfia : hojas 46-47
Keywords: Inglés -- Enseñanza